Mechanical Properties of Mortar with Anadara Granosa Waste as Partial Sand Replacement - Hanis Nadiah, Ruslan; Khairunisa, Muthusamy; Mohd Faizal, Md Jaafar; Nur Azzimah, Zamri; Ramadhansyah, Putra Jaya (Bentham Open, 2023)
Introduction: In order to create a cleaner and more sustainable environment, cockle shell waste created from the local fisheries trade is used to produce construction materials, which meet the needs of a developing sustainable construction sector. The use of cockle shell waste as construction materials can help both the environment and the community. Though, the use of this waste as a partial replacement for fine aggregate (sand) in mortar has received little attention. Aims: the current study aims to investigate the influence of Anadara granosa (cockle shell) as a fine aggregate substitute on the mechanical properties of mortar namely compressive strength, flexural strength, and dynamic modulus elasticity. Methods: In this study, the cockle shell is crushed to fine particles and then integrated as fine aggregate replacement in various ratios of 10, 20, 30, and 40%. Results: The result indicated that integrating 10% crushed cockle shell into mortar enhances its compressive strength, flexural strength, and modulus elasticity when compared to the control mortar. Conclusion: Conclusively, success in utilizing cockle shells as sand in mortar can help to reduce environmental problems and produce sustainable construction material.